Bispecific antibodies revolutionizing breast cancer treatment: a comprehensive overview - Lan, Huan-Rong; Chen, Min; Yao, Shi-Ya; Chen, Jun-Xia; Jin, Ke-Tao (Frontiers in Immunology, 2023)
Breast cancer (BCa) is known as a complex and prevalent disease requiring the development of novel anticancer therapeutic approaches. Bispecific antibodies (BsAbs) have emerged as a favorable strategy for BCa treatment due to their unique ability to target two different antigens simultaneously. By targeting tumor-associated antigens (TAAs) on cancer cells, engaging immune effector cells, or blocking critical signaling pathways, BsAbs offer enhanced tumor specificity and immune system involvement, improving anti-cancer activity. Preclinical and clinical studies have demonstrated the potential of BsAbs in BCa. For example, BsAbs targeting human epidermal growth factor receptor 2 (HER2) have shown the ability to redirect immune cells to HER2-positive BCa cells, resulting in effective tumor cell killing. Moreover, targeting the PD-1/PD-L1 pathway by BsAbs has demonstrated promising outcomes in overcoming immunosuppression and enhancing immune-mediated tumor clearance. Combining BsAbs with existing therapeutic approaches, such as chemotherapy, targeted therapies, or immune checkpoint inhibitors (ICIs), has also revealed synergistic effects in preclinical models and early clinical trials, emphasizing the usefulness and potential of BsAbs in BCa treatment. This review summarizes the latest evidence about BsAbs in treating BCa and the challenges and opportunities of their use in BCa.